Medicine on the edge of the Habsburg territories : medical practices and medical care at the Banat military border (late 18th century - early 19th century) = Medicina na rubu habsburških teritorija : medicinska praksa i medicinska njega na vojnoj granici Banata (krajem 18. - početkom 19. stoljeća) - Hirsch, Sandra (Array, 2021)
Designed as a defensive system against the Ottoman Empire, the Austrian military border was doubled by a sanitary cordon, which served as a defense shield against epidemics. In order for this system to function adequately, the border patrol troops that served the House of Habsburg also needed protection against the diseases that threatened the empire. The present study brings into discussion the health problems that border guards from the Banat region experienced, a topic that remains largely unaddressed in the existing literature. By building on original archival research and the specialized work of the epoch, this article traces the main conditions, the means of tackling diseases, the remedies that were specifically local or those found within the European repertoire. It also sheds light on the support that the administrative apparatus offered to the troops, namely medical care in its material form (hospitals, quarantines, pharmacies, medicine, monetary assistance) and human form (the personnel hired at the borders: military doctors, surgeons, midwives, veterinarians). This article concludes that the entire correspondence from the center directed at the local authorities in Banat and vice versa reflects in a unique and subtle way the level of medical knowledge of the time.